Perioperative Pulmonary Atelectasis: Part I. Biology and Mechanisms. (8th September 2021) - Zeng, Congli; Lagier, David; Lee, Jae-Woo; Vidal Melo, Marcos F.
Abstract : Pulmonary atelectasis is common in the perioperative period. Physiologically, it is produced when collapsing forces derived from positive pleural pressure and surface tension overcome expanding forces from alveolar pressure and parenchymal tethering. Atelectasis impairs blood oxygenation and reduces lung compliance. It is increasingly recognized that it can also induce local tissue biologic responses, such as inflammation, local immune dysfunction, and damage of the alveolar–capillary barrier, with potential loss of lung fluid clearance, increased lung protein permeability, and susceptibility to infection, factors that can initiate or exaggerate lung injury. Mechanical ventilation of a heterogeneously aerated lung ( e.g., in the presence of atelectatic lung tissue) involves biomechanical processes that may precipitate further lung damage: concentration of mechanical forces, propagation of gas–liquid interfaces, and remote overdistension. Knowledge of such pathophysiologic mechanisms of atelectasis and their consequences in the healthy and diseased lung should guide optimal clinical management. Abstract : Up-to-date information on the pathophysiological mechanisms producing atelectasis and its functional, biologic, and biomechanical consequences is reviewed. The mechanistic understanding aims to provide a solid basis for critical assessment of clinical management.